LOCAL EXISTENCE AND GLOBAL NONEXISTENCE FOR A SYSTEM f OF NONLINEAR WAVE EQUATIONS WITH p-LAPLACIAN OPERATOR - Quispe Méndez, Teófanes (2012)
We consider a mixed problem for a system of nonlinear wave equations with p-Laplacian operator and with dissipative strong term. We prove the local existence of solutions by Galerkin method and blow-up of' solutions by the energy method. We give some estimates for' the life span of solutions.